IMPLEMENTASI METODE PEMBELAJARAN PQ4R MATERI ENERGI TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 060879 MEDAN TIMUR: Penelitian Tindakan Kelas - Edwin Rejeki Nababan; Jhonas Dongoran (STKIP Subang, 2025)
This research is motivated by the low learning outcomes of students in grade IV of SD N 060879 Medan Timur, especially in science subjects. This study aims to improve learning outcomes through the integration of the PQ4R learning method (Preview, Question, Read, Reflect, Recite, Review). This research is a classroom action research conducted in 2 cycles with the research subjects being 34 grade IV students. The data collection technique is using a test assessment sheet. The results of the study indicate that the PQ4R method has an impact on improving student learning outcomes. This can be seen from the learning outcomes before using PQ4R 38.23% so that based on these results it has not reached completion. During learning with the PQ4R method, the use of cycle I obtained student learning outcomes of 55.8% and in cycle II obtained learning outcomes of 91.17%. Thus, the implementation of the PQ4R method has proven effective in improving learning outcomes in the material of energy transformation.